(untitled) (Bangladesh Medical Journal, 2016)
Polycystic ovarian syndrome (PCOS) is a common disorder for female with fertile age. Along with other clinical and biochemical manifestations, thyroid function and prolactin level may be altered in patients with PCOS. This study aimed to evaluate the clinical and biochemical status, as well as alteration of thyroid stimulating hormone (TSH), prolactin (PRL) level in patients with PCOS. Present study comprised of 100 diagnosed PCOS patients according to revised Rotterdem Consensus criteria. All patients were studied for serum testosterone, LH (lutenizing hormone), FSH (follicle stimulating hormone), blood glucose, lipid profile as well as TSH, FT4 (free thyroxin) and prolactin level. Out of 100 PCOS patients 97 had hirsutism, 64 had acanthosis nigricans, where menstrual irregularities were in 94 patients. Diastolic blood pressure (74±1.1 vs. 77±0.9, mmHg; p=0.017), total cholesterol (163±5.3 vs. 193±6.2 mg/dl; p<0.001), low density lipoprotein (LDL, 104±3.7 vs. 124±4.9 mg/dl; p=0.002) and frequency of acanthosis (25% vs. 75%; p<0.001) were significantly higher among the patients having BMI>25 Kg/m2 than those of have ? 25 Kg/m2. Among the fertile women (n=53), 47% had primary and 41.5% had secondary infertility; whereas of the total patients, 21% had altered thyroid function and 6.1% had raised prolactin (PRL, ng/ml) level. Differences of TSH (4.1±3.6 vs. 3.5±6.8, mIU/L; p=0.725) was not significant; whereas level of PRL (13.87±6.9vs. 9.4±5.2 ng/ml; p=0.018) was significantly higher in the group of primary infertility. Hirsutism, menstrual disturbance and acanthosis were very common in PCOS. Both primary and secondary sterility were also commonly observed and PRL was higher in primary infertility. About one fifth of PCOS had altered thyroid function. Bangladesh Med J. 2016 Jan; 45 (1): 1-5